THE ROLE OF TOURISM IN THE DEVELOPMENT OF THE COUNTRY’S ECONOMY - Akbarov Davronbek Ikromovich; Nurmatova Zaxro Nosirjon qizi; Abdurashidov Baxrombek Abdullajon o’g’li (Galaxy International Interdisciplinary Research Journal, 2022)
In the article, Tourism may have a positive economic impact on the balance of payments, on employment, on gross income and production, but it may also have negative effects, particularly on the environment. Unplanned and uncontrolled tourism growth can result in such a deterioration of the environment that tourist growth can be compromised. The environment, being the major source of tourist product, should therefore be protected in order to have further growth of tourism and economic development in the future. This is specially true with regard to tourism based on the natural environment as well as on historical-cultural heritage.